Aid for trade in Asia and the Pacific : promoting connectivity for inclusive development. (Asian Development Bank Institute, 2017)
The role of Aid for Trade (AfT) in promoting the growth and tradability of services is important, given that it is a major catalyst for inclusive economic and structural transformation. This report highlights emerging trends in AfT in the context of evolving trade performance in Asia and the Pacific. In particular, the impact of AfT on trade in services, thereby helping increase economic and job opportunities for women, and the rise of e-commerce. The report ends by considering policy implications of the experiences of geographically-challenged economies of the region along the dimensions of trade costs, AfT, trade in services, and the role of the digital economy.